Hukum Euthanasia dalam Pandangan Islam - Syafrida Ayu Sari; Darania Anisa (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Euthanasia and suicide are complex ethical and legal issues, especially in a religious context. Suicide is an act of destroying oneself by using substances (poison/drugs) which results in death. A person commits suicide due to frustration and considers that suicide is the only alternative to change his life and that death is not the opposite of life. This research aims to analyze Islamic views on the practice of euthanasia and suicide. Through an in-depth study of the Quran, hadith, and opinions of ulama, this research concludes that both euthanasia and suicide are strictly prohibited in Islam. This prohibition is based on the belief that life is a gift from Allah SWT that should not be taken carelessly. This research also discusses the legal and ethical implications of this prohibition in the context of modern society.